Subchondral bone plate remodels more rapidly than trabecular bone in osteoarthritis - Zamli, Zaitunnatakhin; Robson Brown, Kate; Tarlton, John F.; Sharif, Mohammed (Elsevier, 2015)
Objective: To determine the sequence and the relationship between bone remodelling in subchondral bone plate (Sbp) and trabecular bone (Tb), during the development of OA in two spontaneous animal models, the Dunkin Hartley (DH) guinea pig which develop OA around 12 weeks and the Bristol Strain 2 (BS2) which develops OA around 24 weeks of age.